2017
DOI: 10.1680/jstbu.16.00013
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and extreme wind effects on transmission towers

Abstract: Climate change poses a major threat to electricity power infrastructure due to expected increase in magnitude and frequency of extreme storm events. This paper uses a methodology for assessment of the vulnerability of UK transmission tower infrastructure to such events, within a framework of performance based engineering.The challenge of estimating future storm magnitudes is addressed by applying a Change Factor Methodology to present day wind speeds using information provided by 2009 UK Climate Change Project… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The first block is the energy-transmission block, responsible for transporting electricity over long distances through high-voltage lines. The second block enables distribution, delivering electricity to end users through substations and distribution lines [28]. This layer is interconnected through various layers such as the communication layer, the consumer-interaction layer, the automation and control layer, and the data-management layer to prevent energy losses, maintain a self-healing network, and analyze data to detect cybersecurity threats against electrical systems that could have physical impacts on the electrical layer [29].…”
Section: Electrical-infrastructure Layermentioning
confidence: 99%
“…The first block is the energy-transmission block, responsible for transporting electricity over long distances through high-voltage lines. The second block enables distribution, delivering electricity to end users through substations and distribution lines [28]. This layer is interconnected through various layers such as the communication layer, the consumer-interaction layer, the automation and control layer, and the data-management layer to prevent energy losses, maintain a self-healing network, and analyze data to detect cybersecurity threats against electrical systems that could have physical impacts on the electrical layer [29].…”
Section: Electrical-infrastructure Layermentioning
confidence: 99%
“…Research conducted by Manis and Bloodworth [26] indicated that for the case of UK transmission towers it is the 45 degree wind orientation that gives lower load capacity of the tower due to one leg becomes more heavily loaded in compression rather than two. Previous design experience indicated that, for those towers without influence by mining subsidence, the 45 degree wind orientation normally gives failure of tower's leg while the 90 degree wind orientation gives failure of X-cross bracing members.…”
Section: Load and Support's Displacementmentioning
confidence: 99%
“…They shed light on technical problems usually dealt with in current engineering practice.The first paper in this issue, authored by Manis and Bloodworth (2017), assesses the safety of UK transmission tower infrastructure under extreme wind loading. They evaluate the storm magnitudes by applying a change factor methodology to present day wind speeds and using the information provided by the 2009 UK climate change projections.…”
mentioning
confidence: 99%